Networking with LANtastic - Montgomery, Michael S. 1955- (Windcrest/McGraw-Hill, 1992)
Focusing on ways to configure LANtastic networks to meet specific needs and ensure maximum workstation productivity, this book explains how to plan and design networks, install LANtastic software, and use program functions and menus.